CRISPR/Cas9-Targeted Myostatin Deletion Improves the Myogenic Differentiation Parameters for Muscle-Derived Stem Cells in Mice - Mohamed I. Elashry; Victoria C. Schneider; Manuela Heimann; Sabine Wenisch; Stefan Arnhold (Journal of Developmental Biology)
Skeletal muscle plays a pivotal role in physical activity, protein storage and energy utilization. Skeletal muscle wasting due to immobilization, aging, muscular dystrophy and cancer cachexia has negative impacts on the quality of life. The deletion of myostatin, a growth and differentiation factor-8 (GDF-8) augments muscle mass through hyperplasia and hypertrophy of muscle fibers. The present study examines the impact of myostatin deletion using CRISPR/Cas9 editing on the myogenic differentiation (MD) of C2C12 muscle stem cells. A total of five myostatin loci were targeted using guided RNAs that had been previously cloned into a vector. The clones were transfected in C2C12 cells via electroporation. The cell viability and MD of myostatin-edited clones (Mstn−/−) were compared with C2C12 (Mstn+/+) using a series of assays, including MTT, sulforhodamine B, immunocytochemistry, morphometric analysis and RT-qPCR. The clones sequenced showed evidence of nucleotides deletion in Mstn−/− cells. Mstn−/− cells demonstrated a normal physiological performance and lack of cytotoxicity. Myostatin depletion promoted the myogenic commitment as evidenced by upregulated MyoD and myogenin expression. The number of MyoD-positive cells was increased in the differentiated Mstn−/− clones. The Mstn−/− editing upregulates both mTOR and MyH expression, as well as increasing the size of myotubes. The differentiation of Mstn−/− cells upregulates ActRIIb; in contrast, it downregulates decorin expression. The data provide evidence of successful CRISPR/Cas9-mediated myostatin deletion. In addition, targeting myostatin could be a beneficial therapeutic strategy to promote MD and to restore muscle loss. In conclusion, the data suggest that myostatin editing using CRISPR/Cas9 could be a potential therapeutic manipulation to improve the regenerative capacity of muscle stem cells before in vivo application.